2014
DOI: 10.1017/s1751731114000263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term oilseed supplementation on plasma fatty acid composition, progesterone and prostaglandin F metabolite in lactating beef cows

Abstract: Twenty-four 3-year-old Angus cows (512.2 ± 21.6 kg) and six ruminally cannulated beef heifers (523.1 ± 16.9 kg) were used to determine the impact of feeding oilseeds starting at the beginning of estrous synchronization until maternal recognition of pregnancy on plasma fatty acid composition. Starting~60 days postpartum cows were synchronized with the Select Synch + controlled internal drug-release (CIDR) device and timed artificial insemination (AI) protocol. The day CIDR was inserted; cattle were randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…n-3 PUFA supplementation in the current study had no effect on plasma concentrations of P4, in contrast to the observations of Childs et al [11] who reported evidence of an increase in overall P4 output as well as greater size of CL and cholesterol concentrations in animals fed a high n-3 PUFA diet. Indeed, the literature relating to effects of PUFA supplementation on systemic concentrations of P4 is inconsistent with reports of an increase [11], decrease [56][57][58] or no change [39,45,[59][60][61]. The findings of Lopes et al [62] suggest that feeding 0.1 kg/d of a rumen-inert PUFA supplement to ovariectomized, non-lactating, beef cows reduced hepatic P4 metabolism.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…n-3 PUFA supplementation in the current study had no effect on plasma concentrations of P4, in contrast to the observations of Childs et al [11] who reported evidence of an increase in overall P4 output as well as greater size of CL and cholesterol concentrations in animals fed a high n-3 PUFA diet. Indeed, the literature relating to effects of PUFA supplementation on systemic concentrations of P4 is inconsistent with reports of an increase [11], decrease [56][57][58] or no change [39,45,[59][60][61]. The findings of Lopes et al [62] suggest that feeding 0.1 kg/d of a rumen-inert PUFA supplement to ovariectomized, non-lactating, beef cows reduced hepatic P4 metabolism.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In another study the dietary treatments had no effect on pregnancy rates, but the levels of plasma prostaglandin F and serum progesterone were affected (Richardson et al, 2013;Scholljegerdes et al, 2014). The prostaglandins are a group of hormone-like lipid compounds that are derived enzymatically from fatty acids and have a variety of strong physiological effects, such as regulating the contraction and relaxation of smooth muscle tissue.…”
Section: Seeds and Oilmentioning
confidence: 99%
“…Linseed as a source of n-3 fatty acids has been widely used as it is well known that linseed is rich in α-linolenic acid (Scholljegerdes et al, 2014). Apart from milk composition, n-3 fatty acids can influence immune response and reduce symptoms of chronic inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%